Cryptic Early Gastric Carcinoma in Gastric Stump: Challenges in Diagnostic Evaluation - Subramanya Sakaleshpura Mallikarjunappa; Shriram Jakate (Hindawi Limited, 2019)
Partial gastrectomy, performed for any indication, is a well-recognized risk factor for carcinoma developing in the gastric remnant (so-called "gastric stump carcinoma"). In symptomatic patients with gastro-enteric anastomosis, it is a common practice to endoscopically evaluate the patency and the status of the anastomosis and procure biopsy samples when endoscopic abnormalities are noted. We describe a case with Billroth I gastroduodenal anastomosis with oozing and friability at the anastomosis site which was biopsied. The biopsies showed invasive intestinal-type adenocarcinoma. Subsequent completion gastrectomy showed no grossly visible tumor and required extensive initial and additional sampling of the anastomosis and the surrounding stomach to locate a small focus of invasive adenocarcinoma limited to the mucosa ("early gastric carcinoma"). This case illustrates a known complication of partial gastrectomy and highlights challenges in diagnostic evaluation of early gastric carcinoma after gastrectomy.